Determinants of Corporate Social Responsibility (CSR) Company Disclosure in the Non-Cyclical Consumer Sector 2019-2021 - Amanda*, Jesslyn; Suhendah, Rousilita (Universitas Syiah Kuala, 2023)
The aim of this research is to obtain empirical evidence regarding the influence of board composition and ownership structure on a company's CSR disclosure. Board composition is examined into 2 variables, namely board size and independent directors. Meanwhile, the ownership structure is examined into 2 variables, namely managerial ownership and institutional ownership. This research uses data from annual reports and CSR reports of non-cyclical consumer companies on each company's website for the period 2019 to 2021. Data processing uses the EViews 12 application. The results of this research are that board size has a positive influence on CSR disclosure, but directors independence, managerial ownership, and institutional ownership have no effect on CSR disclosure. The results of this research can be considered by investors in providing investment funds, namely by looking at the level of company CSR disclosure based on the composition of the board and ownership structure of the company.